The impact of childhood trauma on adolescent depression: the moderating role of sensory processing sensitivity - Yang, Qianrong; Tao, Yachen; Xie, Mei; Long, Quanyi; Zhu, Zhi; Hu, Qijun; Zhou, Meng; Zou, Yuanyuan; Li, Xuzhou (Frontiers in Psychology, 2025)
This study investigated the relationship between childhood trauma and adolescent depression, with a particular focus on the moderating role of sensory processing sensitivity (SPS) and its specific subdimensions. A cross-sectional survey was conducted among 843 high school students in China, utilizing the Childhood Trauma Questionnaire (Short Form), the 21-item Highly Sensitive Child Scale, and the Center for Epidemiological Studies Depression Scale. Results indicated that childhood trauma significantly predicted depressive symptoms in adolescents. Moreover, SPS moderated the association between childhood trauma and depression, with higher SPS amplifying the adverse effects of trauma. Further analyses revealed that the three SPS dimensions—Ease of Excitation (EOE), Low Sensory Threshold (LST), and Aesthetic Sensitivity (AES)—each demonstrated unique moderating effects. These findings advance current understanding by illustrating how distinct facets of sensitivity shape vulnerability to depression following childhood trauma. The results offer theoretical contributions to developmental psychopathology and suggest practical implications for designing individualized, sensitivity-informed interventions to support adolescents at risk of depression.